Health-related quality of life and family functioning of primary caregivers of children with down syndrome - Rozensztrauch, Anna; Wieczorek, Karolina; Twardak, Iwona; Śmigiel, Robert (Frontiers in Psychiatry, 2023)
Background: Down Syndrome (DS; OMIM #190685), known as trisomy 21, is one of the most common genetic disorders in the human population and the commonest known cause of intellectual disability. The study was conducted to investigate the quality of life (QoL) of children with DS syndrome and its impact on family functioning.To assess the quality of life of children with trisomy 21 and the impact of the disorder on the family.We used a cross-sectional questionnaire study. The respondents were 52 parents of children with trisomy 21. The following structured questionnaires were used: the PedsQL TM 4.0 Generic Core Scales, the PedsQL TM Family Impact Module and Study-Specific Questionnaire (SSQ).The combined scores, with a mean value of approximately 55 out of a possible 100 points, indicated a significant impact of the child's genetic defect on family functioning. In the overall QOL, the highest rated domain was physical functioning (x ̅ =60.14; SD=23.82) and the lowest was school functioning (x ̅ =51.36; SD=18.72). Better school functioning (p=0.022) was reported for girls. The presence of reduced muscle tone also had a negative impact on the child's functioning in the physical (p=0.036), emotional (p=0.011), psychosocial (p=0.027) and overall QOL domains (p=0.023).Conclusions: Overall, our results showed that the quality of life of children with trisomy 21 is impaired. There was a positive association between the child's QOL and the QOL of their parents, as well as the general functioning of the child's whole family. For this reason, an improvement in the QOL of parents and the family functioning is closely related to an increased QOL of the child. The 2 This is a provisional file, not the final typeset article continuous deepening of knowledge of QOL in individual trisomy 21 management allows for better preparation and ongoing care for the patients concerned.